Educational Leadership Through a Pasifika Lens: Navigating Their Way in a New Zealand Secondary School Context - Brown, Mary (Auckland University of Technology, 2019)
There is an under-representation of Pasifika teachers in New Zealand secondary schools. Research has shown that educational leadership should be responsive and reflective to the communities they serve, and although indigenous leadership research is growing, it is still limited in comparison to the more westernised notions of leadership. The following research study aims to determine the aspirations of Pasifika leaders leading in New Zealand secondary schools. Building on existing literature on Pasifika leadership, it asks: To identify the ways in which Pasifika teachers aspire for secondary school leadership; and to identify and critically examine Pasifika teacher’s perspectives of the enablers/challenges faced in moving into secondary school leadership. Based on a review of the literature on Educational leadership, Indigenous leadership and aspirations to leadership. Research participants shared their leadership journey through the research methodology of a narrative approach. Analysis of the findings show that each narrator was initially reluctant in their leadership journey, however the common enablers identified were having strong family networks and role models who believed in them. Challenges faced as they navigated through their leadership were bias expectations as Pasifika and reference to the ‘glass ceiling’. In this context, the ‘glass ceiling’ is referred to an unseen barrier that often keeps women and minority groups such as Pasifika from being promoted because of attitudinal and organisational obstacles that stop the progression of non-traditional leaders (Levine, 2000). The results point out that supportive systems in leadership progression responsive to the socio-cultural context can make a difference. The recommendation is that New Zealand secondary schools prioritise an inclusive leadership approach to change the status-quo of traditional leadership which often marginalises the opportunities of non-dominant groups. Further research is needed on Pasifika educational leadership in New Zealand schools to shift and progress in diversifying leadership to mirror the communities they lead in.
Keywords: Educational leadership; Pasifika; Indigenous; Secondary school